Optical and thermal characterization of silver nanoparticles dispersion in lamellar liquid crystal matrix - Mohd Yasin, Siti Mariah; Johan, Mohd Rafie (Elsevier, 2019)
The lamellar lyotropic liquid crystal (LLLC) was used as a host to assemble silver nanopar- ticles (AgNPs) through in situ technique. At first, a mixture of HDTABr/1-pentanol/water was prepared to observe the liquid crystal texture via polarizer microscope. The lamellar texture with intensely arrangement at lower water content was observed, that was also similar texture by replacing Ag solution at lower volume. The UV–vis showed surface plasmon resonance bands were influenced by the concentration of AgNO3. Transmission electron microscopy (TEM) showed nanoparticles were nearly monodispers with an average particles size 4–5 nm at lower Ag+ meanwhile produced even larger with separate aggregate, ∼11 nm average particles size at the highest concentration Ag solution. The emission peaks were enhanced as the AgNO3 concentrations increased. Thermal studies showed evidently most stable at 710 °C for highly concentrated nanoparticles.